2023
DOI: 10.3389/fmicb.2023.1232323
|View full text |Cite
|
Sign up to set email alerts
|

Yeast strains do have an impact on the production of cured cocoa beans, as assessed with Costa Rican Trinitario cocoa fermentation processes and chocolates thereof

Abstract: The microbiological and metabolic outcomes of good cocoa fermentation practices can be standardized and influenced through the addition of starter culture mixtures composed of yeast and bacterial strains. The present study performed two spontaneous and 10 starter culture-initiated (SCI) cocoa fermentation processes (CFPs) in Costa Rica with local Trinitario cocoa. The yeast strains Saccharomyces cerevisiae IMDO 050523, Hanseniaspora opuntiae IMDO 020003, and Pichia kudriavzevii IMDO 060005 were used to compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 162 publications
0
2
0
Order By: Relevance
“…As edible microorganisms, lactic acid bacteria and yeast have bright application prospects. Presently, many food-grade, genetically engineered microorganisms have been successfully constructed, and they have been applied in health care, fermentation, food processing, and other fields ( Abrha et al 2023 ; González-Orozco et al 2023 ; Van de Voorde et al 2023 ). The selection markers on vectors are an important part of the selection system for recombinant microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…As edible microorganisms, lactic acid bacteria and yeast have bright application prospects. Presently, many food-grade, genetically engineered microorganisms have been successfully constructed, and they have been applied in health care, fermentation, food processing, and other fields ( Abrha et al 2023 ; González-Orozco et al 2023 ; Van de Voorde et al 2023 ). The selection markers on vectors are an important part of the selection system for recombinant microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that from the fifth day of fermentation the temperature did not vary, reaching a temperature between 40-50 °C, a desirable range for good fermentation [39]. On the other hand, from the third day of fermentation the mass recorded an increase in pH, a situation attributed to the decrease by leaching of citric acid contained in the pulp [40] and the decrease of volatile organic acids leading to an increase in pH in the fermentation mass [41] as to the metabolization of citric acid by the yeasts [42]. This decrease in pH within the first few days at all sites is attributed mainly to the diffusion of organic acids in the bean produced by lactic acid bacteria [43] and together with the high temperatures, which lead to embryo death, triggering a series of biochemical changes that greatly impact the development of bean flavor and color.…”
Section: Temperature and Ph Of Fermented Cocoa Beansmentioning
confidence: 97%